2012
DOI: 10.2208/kaigan.68.i_576
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic of shoreline response to cyclic tidal change

Abstract: The responses of the shoreline change to cyclic tidal changes were investigated by the spectral analysis using FFT method and a multivariate autoregressive model. The shoreline data set were obtained for 25 years at Hazaki Oceanographical Research Station (HORS) facing the Pacific Ocean. The power spectrum densities showed shoreline changes with a period of 14.76 days, which is the spring-neap cycle of the tide. The relative power contribution analysis showed the tidal range affects the shoreline change rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For simplicity, we took one (average) frequency for the semidiurnal and dirnurnal peaks. At lower frequencies, in addition to these two peaks, we need another 3rd component (one-year periodicity) (Banno, Kuriyama 2012), since the |H(f)| 2 takes a constant value, without the 3rd component. Overall fitting of the Lorentz oscillator, including the 3rd constituent, to the practical data is reasonably good.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For simplicity, we took one (average) frequency for the semidiurnal and dirnurnal peaks. At lower frequencies, in addition to these two peaks, we need another 3rd component (one-year periodicity) (Banno, Kuriyama 2012), since the |H(f)| 2 takes a constant value, without the 3rd component. Overall fitting of the Lorentz oscillator, including the 3rd constituent, to the practical data is reasonably good.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the tide levels are dominated Tide level in time and frequency domains... by four major gravitational constituents from the sun and the moon (M2, S2, K1, O1) and tide level dynamics is replicated well by the Lorentz-type resonance (Wooten 1972). The FS shows two principal peaks (diurnal and semidiurnal) (Ro 2007;Stewart 2008) and another constituent (one year), together with a 1/f-like characteristics at higher frequencies (Banno, Kuriyama 2012;Kogan 2008). It is also shown that the histogram of the tide level observed in time domain is approximated to be a Gaussian distribution function.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations